PENGKAYAAN TARI GANDRUNGAN GAGAH GAYA SURAKARTA - Suharji, S., (Institut Seni Indoensia Surakarta, 2016)
The aim of research entitled Enrichment Dance Gandrungan Gagah Surakarta style is to describeÂ the dance gandrungan gagah Surakarta style. The target achieved of the research is an improvementÂ of textbooks in 2014. The method used is librarian study that studies the books that have been published in advance. Some flaws in the book and then enhanced by adding dance gandrungan differentÂ characters. Model analysis using interpretive narrative. The results were obtained additional repertoire of dance descriptions gandrungan Garuda Yaksa and Niwatakawaca gandrung. Previous research has been completed Gathutkaca dance, Kelana, Menakjingga gandrung. Overall a description gandrungan gagah dance Surakarta styles include Gathutkaca Kelana, Menakjingga, GarudaYaksa and Niwatakawaca gandrung.Keywords: gandrungan, gagah, dance, Surakarta.